BIGGER IS NOT ALWAYS BETTER: CONFLICTING SELECTIVE PRESSURES ON SEED SIZE IN QUERCUS ILEX (Evolution, 2004)
Abstract Most theoretical treatments of the evolutionary ecology of offspring size assume a simple and direct effect of investment per offspring on offspring fitness. In this paper I experimentally determine the relationship between seed mass and several main fitness components of the oak Quercus ilex, to estimate phenotypic selection acting on seed mass during the early life cycle and to discover any potential selective conflicts occurring between different stages from dispersal to establishment. I found a positive effect of acorn size on most fitness components related to seedling establishment. Large size increased germination rate and seedling survival, accelerated germination timing, and enhanced seedling growth. Nevertheless, there was also a direct negative effect of acorn size on survival to predation, because large acorns were highly preferred by the main postdispersal seed predators at the study site, wild boars and wood mice. Because of the low probability of escape from predation, the fitness of large acorns estimated on this component was significantly lower than the fitness of smaller acorns. Therefore, seed size affected fitness in two different ways, yielding opposing and conflicting selective forces. These findings suggest that the general assumption that offspring fitness is a fixed positive function of seed size needs to be reconsidered for some systems. The existence of conflicting selection might explain the occurrence of an optimal seed size in some plant species without invoking a seed number-size trade-off.